Evaluation of sodium content and sodium hydroxide molarity on compressive strength of alkali activated low-calcium fly ash. (August 2017) - Bhagath Singh, G.V.P.; Subramaniam, Kolluru V.L.
Abstract: Activation of low calcium fly ash is investigated using activating solutions of sodium hydroxide (NaOH) and sodium silicate (Na2 SiO3 ). The oxide ratio of Na2 O relative to the total reactive silica in the activated mix provides consistent results in achieving the highest ultimate strength. The total reactive silica used for calculating the ratio consists of the reactive silica contributed by fly ash and the silica from the activating solution. There is an increase in the ultimate compressive strength on increasing the total sodium content relative to the total reactive silica content in the activated system. Increasing the sodium content beyond a certain limit does not provide additional gain in the ultimate compressive strength. The ratio of total reactive SiO2 to Na2 O in the activated system equal to 4.72 is shown to provide the highest compressive strength and there is no further increase in the ultimate strength on increasing the sodium content. A N-A-S-H type gel with reaction products containing Si, Al and Na, is formed in the activated system. The ultimate strength achieved is directly related to the reaction product content in the system and is dependent on the extent of glassy phase dissolution from fly ash. The extent of glassy phase dissolution and the quantity of reaction product formed in the system increases with an increase in the molarity of NaOH, which also contributes to an increase in the sodium content in the activating solution. The decrease in the unreacted glassy phase content of fly ash is sensitive to temperature at a lower molarity of NaOH. The Al/Na ratio in the reaction product approaches a value of 0.9 on increasing the sodium content in the activated system. The Si/Al ratio in the reaction product varies within a range of 2.3–2.8.